Does Employee-Related Factors Success Mediate To The MSME’s Marine Products Business? - Ian Nurpatria Suryawan (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2024)
Employee-related factors include recruiting and empowering individuals with diverse backgrounds. This study aims to identify the characteristics that impact employee performance. The sampling technique used in this research is cluster random sampling based on region. Questionnaires were randomly distributed to 90 employees from a population exceeding 600 marine products SMEs in the North Jakarta coastal area. The respondents included 54 male and 36 female employees, aged between 18 and 45 years, with work experience ranging from 1 to 5 years. The test results indicate that firm-related factors positively but less significantly affect employee performance. In contrast, other hypotheses show a positive and significant impact. Employee-related factors mediate the influence of firm-related factors on employee performance and job-related factors on employee performance.